Advanced isolated light chain amyloid cardiomyopathy with negative immunofixation and normal free light chain ratio. (7th May 2021) - Zach, David; Ablasser, Klemens; Kolesnik, Ewald; Hoeller, Viktoria; Fruhwald, Friedrich; Prüller, Florian; Reiter, Clemens; Beham‐Schmid, Christine; Lipp, Rainer; Rainer, Peter P.; Zirlik, Andreas; Wölfler, Albert; et al.
Abstract: Amyloid light chain (AL) cardiomyopathy is the most malignant specific cardiomyopathy. According to international recommendations, it should be ruled out non‐invasively using the serum free light chain (FLC) ratio and immunofixation electrophoresis in both serum and urine. Here, we report on a 69‐year‐old female patient with new‐onset heart failure with mid‐range ejection fraction. Cardiac imaging was highly suggestive of cardiac amyloidosis. Amyloid scintigraphy showed faint myocardial tracer uptake according to Perugini Score 1, but immunofixation was negative and the FLC ratio was normal, despite a slight increase in lambda FLCs. Endomyocardial biopsy revealed advanced myocardial lambda immunoglobulin light chain deposition. Clinically relevant extracardiac amyloid organ infiltration could not be detected. Conclusively, non‐invasive testing can in rare cases fail to exclude isolated AL amyloid cardiomyopathy. We suggest that even slight increases in serum lambda or kappa FLCs should be considered abnormal in suspected cardiac amyloidosis if non‐invasive testing delivers discrepant results.